MARITIME VIOLENCE : IMPLICATIONS TO MALAYSIA - Nurulizwan Ahmad Zubir (Arena Hukum, 2012)
AbstractMaritime Piracy has been a serious threat to the international community especially in the SoutheastAsia region. This threat has caused tremendous implications towards the world economy, environment,political stability of the nations involved because 45% of the shipping company passes through theSoutheast Asia. The worrying fact is that these attacks were committed by terrorists as well as traditionalmaritime pirates. This paper examines on the implications of maritime crime in Malaysia and discusseswhether the definition of piracy under the International Law could be applied to these attacks. Thispaper concludes that cooperation between the region’s states and the enhancement of a good securitysystem of one state are needed to combat maritime violence. Thus it is imperative that the internationallaw need to be changed in order to enhance the meaning of piracy and also to include sea terrorism.Key words: piracy, maritime, terrorist